Changes in albuminuria and the risk of major clinical outcomes in diabetes: Results From ADVANCE-ON. - Jun, M; Ohkuma, T; Zoungas, S; Colagiuri, S; Mancia, G; Marre, M; Matthews, D; Poulter, N; Williams, B; Rodgers, A; Perkovic, V; Chalmers, J; et al. (American Diabetes Association, 2017)
Objective To assess the association between two-year changes in urine albumin-to-creatinine ratio (UACR) and the risk of clinical outcomes in type 2 diabetes (T2DM). Research design and methods We analyzed data from 8766 participants in the ADVANCE-ON study. Change in UACR was calculated from UACR measurements two years apart, classified into three groups: decrease in UACR of ≥30%, minor change and increase in UACR of ≥30%. By analyzing changes from baseline UACR groups, categorized into thirds, we repeated these analyses accounting for regression to the mean (RtM). The primary outcome was the composite of major macrovascular events, renal events and all-cause mortality; secondary outcomes were these components. Cox regression models were used to estimate hazard ratios (HRs). Results Over a median follow-up of 7.7 years, 2191 primary outcomes were observed. Increases in UACR over two years independently predicted a greater risk of the primary outcome (HR for ≥30% UACR increase versus minor change: 1.26, 95% confidence interval [CI]: 1.13-1.41) while a decrease in UACR was not significantly associated with lower risk (HR 0.93, 95% CI: 0.83-1.04). However, after allowing for RtM, the effect of “real” decrease in UACR on the primary outcome was found to be significant (HR 0.84, 95% CI: 0.75-0.94), whilst the estimated effect on an increase was unchanged. Conclusions Changes in UACR predicted changes in the risk of major clinical outcomes and mortality in T2DM, supporting the prognostic utility of monitoring albuminuria change over time.